Být připraven, znamená přežít! Metodický materiál k výuce ochrany člověka za mimořádných událostí pro 2. stupeň základních škol - první pomoc v OČMU - Lízalová, Vanda (Masaryk University Press, 2022)
Title in English: Get Ready and Survive!: Methodology for teaching human protection in emergency situations for lower secondary schools - first aid in human protection in emergency situations 2 The methodology "Get Ready and Survive! Methodology for teaching human protection in emergency situations for lower secondary schools - first aid in human protection in emergency situations 2" is based on the document of the Fire Rescue Service of the Czech Republic "Resource for teaching human protection against usual risks and in emergency situations in elementary schools". The methodology is a resource that complements the methodologies Get Ready and Survive! Part 1 (Slaná Reissmannová, Mertová, 2021) and Get Ready and Survive! Part 2 (Slaná Reissmannová, Lízalová, 2022), provides a theoretical and didactic framework for the topic (first aid in human protection in emergency situations) and serves for the training of students of the study programme Health Education as well as teachers in elementary and secondary schools and universities in teaching this complex and highly topical issue. The methodology contains 10 lessons with a proven structure: theoretical presentation of the topic, detailed lesson plan, worksheets including the key for the teacher and additional activities. In the text, students/teachers will also find numerous online links to the latest professional information.